Crime scene photography - Robinson, Edward M. (Academic Press, 2010)
Crime Scene Photography, Second Edition, offers an introduction to the basic concepts of forensic picture-taking. The forensic photographer, or more specifically the crime scene photographer, must know how to create an acceptable image that is capable of withstanding challenges in court. The photographic theory and principles have to be well grounded in the physics of optics, the how-to recommendations have to work, and the end result must be admissible in court.